Does Using Sigil E-Modules Impact High School Students' Knowledge and Curiosity? A Quantitative Analysis - Ernawati Ernawati; Rini Budiharti; Ahmad Fauzi (Universitas Sebelas Maret, 2024)
This classroom action research has a purpose : (1) Implementing the sigil e-module to increase the knowledge competence of class XI MIPA 5 students at SMA Negeri Kebakkramat for the 2021/2022 Academic Year on temperature, heat, and heat transfer, (2) Implementing the sigil e-module to increase the curiosity of class XI MIPA 5 students at SMA Negeri Kebakkramat for the 2021/2022 academic year on temperature, heat, and heat transfer. The research model used is the model developed by Kemmis and Mc. Taggart went through two cycles. Data collection techniques in this study used observation, questionnaires, tests, interviews, and document review with data analysis techniques in the form of quantitative and qualitative analysis. The results of the study show that the application of a scientific-based sigil e-module to the material temperature, heat, and heat transfer can increase the competence of knowledge and curiosity of class XI MIPA 5 students at SMA Negeri Kebakkramat 2021/2022 Academic Year. The percentage of knowledge competence mastery increased from 33.33% in the pre-cycle to 69.44% in cycle I and increased again to 80.56% in cycle II. The achievement percentage of students' curiosity in the very good and good category increased from 15.38% in the pre-cycle to 80.56% in cycle I and again to 94.44% in cycle II. This research can be the basis for developing Sigil e-module to Temperature, Heat, and Heat Transfer material.